Efficacy of prolonged- and immediate-release tacrolimus in kidney transplantation: a pooled analysis of two large, randomized, controlled trials - Krämer, Bernhard (Transplantation proceedings, 2017)
Background: Two large, prospective studies (12-03; OSAKA) compared the efficacy and tolerability of prolonged-release versus immediate-release tacrolimus in kidney transplant patients also receiving mycophenolate mofetil and low-dose corticosteroids (without induction therapy). Methods. Data were combined into one database to compare results over 24 weeks using 3 alternative endpoints: biopsy-confirmed acute rejection (BCAR); the Food and Drug Administration composite endpoint (graft loss, BCAR, and loss to follow-up), and the European Medicines Agency composite endpoint (graft loss, BCAR, and graft dysfunction). The 95% confidence intervals were calculated (10% noninferiority margin). Results Overall, 633 patients received prolonged-release tacrolimus (12-03, n = 331; OSAKA, n = 302) and 645 received immediate-release tacrolimus (n = 336; n = 309). Baseline characteristics were comparable. Proportionately more patients receiving prolonged-release tacrolimus had trough levels of 5-15 ng/mL on day 1 (60.8%) and 2 (56.6%) versus immediate-release tacrolimus (42.5% and 43.9%, respectively, both P < .001). Efficacy of prolonged-release and immediate-release tacrolimus were similar as assessed by BCAR (13.9% vs 14.1%, respectively), European Medicines Agency composite endpoint (40.3% vs 38.3%) and US Food and Drug Administration composite endpoint (21.5% vs 19.8%). Conclusions Novel efficacy endpoints as required by the European Medicines Agency and US Food and Drug Administration demonstrate noninferiority of prolonged-release versus immediate-release tacrolimus. Significantly more patients treated with prolonged-release tacrolimus versus immediate-release tacrolimus achieved trough levels of 5 to 15 ng/mL early after transplantation. ClinicalTrials.govNCT00189839; NCT00717470.
Gesehen am 08.11.2018